Modelling the impacts of diverse cover crops on soil water and nitrogen and cash crop yields in a sub-tropical dryland - Garba, I.I.; Bell, L.W.; Chapman, S.C.; Voil, P. de; Kamara, A.; Williams, A. (Elsevier, 2023)
Understanding the implications of replacing fallows with cover crops on plant-available water (PAW) and soil mineral nitrogen (N) and their carry-over effects on subsequent cash crops is critical for understanding their potential for ecological intensification in water-limited environments. We modelled the impacts of different cover crop functional types over historical climate to predict how climate variability influences soil water and N acquisition and subsequent availability to a maize crop in a dryland farming system of subtropical Australia. Following local validation of simulation models (APSIM) with 3-site-years of field data, 70 years of crop-fallow rotations were simulated comparing conventional fallow against a diverse range of cover crops comprising monocultures and mixtures of grass vs. legume vs. brassica. Cover crops consistently reduced soil water and mineral N at maize sowing compared to conventional fallow. In dry to normal precipitation years, this induced a maize yield penalty of up to − 18% relative to fallow, primarily due to reduced water availability. In wet years, increased in maize grain yield (+4%) was predicted following legume and grass-associated cover crop mixtures with concomitant reductions in N leaching and soil surface runoff of up to 40%. Cash crop yields following grass-cover crops were more stable and carried lower downside risks; multi-species (grass-legume-brassica) cover crop mixtures carried higher yield penalties and greater downside risks due to high biomass accumulation and high soil water extraction. These long-term predictions in water-limited environments indicate that increasing cover crop complexity by using mixtures with diverse functional traits can lead to a greater risk of yield losses and increased yield instability unless they are managed differently to monoculture cover crops. Therefore, for successful integration of cover crops into dryland agroecosystems, cover crops should be considered as a flexible choice grown under favourable precipitation and economic scenarios rather than for continuous fallow replacement.